The Impact of Logistics Services on the Commodity Trade Structure in United Arab Emirates: An Econometric Study - Tarek, Yalouli; Naim, Ayadi; Sabrina, Grari; Fayza, Dr. Jallouli; Amel, Choutri (The journal of contemporary issues in business and government, 2023)
This study aims to highlight the impact of the logistics services on the commodity trade structure of the UAE. The logistics services represented by (Competence and quality of logistics services, Quality of Trade and Transport Infrastructure, Efficiency and Quality of Logistics Services, and Overall as well as the efficiency of the customs clearance process). ARDL and ARIMA model were used to predict the future values of this standard series, and the relevant data were collected from the World Bank and the Arab Monetary Fund, respectively for the period (2000-2030), after conducting various tests necessary for the distributed autoregressive. This study found an inverse relationship between (Competence and quality of logistics services, Quality of Trade and Transport Infrastructure as well as Efficiency and Quality of Logistics Services) with (commodity trade structure) in the short and long term, in contrast to the variable Efficiency of the customs clearance process, which has a directional relationship in the short and long term, to confirm the vital role played by logistics services on the commodity trade pattern of the Emirates. The study concluded that the of logistics services, reduces the costs and improves the competitiveness of the commodity trade sector of the UAE.